Investigation on Mercury Reemission from Limestone-Gypsum Wet Flue Gas Desulfurization Slurry - Chuanmin Chen; Songtao Liu; Yang Gao; Yongchao Liu (The Scientific World Journal)
Secondary atmospheric pollutions may result from wet flue gas desulfurization (WFGD) systems caused by the reduction of Hg2+ to Hg0 and lead to a damping of the cobenefit mercury removal efficiency by WFGD systems. The experiment on Hg0 reemission from limestone-gypsum WFGD slurry was carried out by changing the operating conditions such as the pH, temperature, Cl− concentrations, and oxygen concentrations. The partitioning behavior of mercury in the solid and liquid byproducts was also discussed. The experimental results indicated that the Hg0 reemission rate from WFGD slurry increased as the operational temperatures and pH values increased. The Hg0 reemission rates decreased as the O2 concentration of flue gas and Cl− concentration of WFGD slurry increased. The concentrations of O2 in flue gas have an evident effect on the mercury retention in the solid byproducts. The temperature and Cl− concentration have a slight effect on the mercury partitioning in the byproducts. No evident relation was found between mercury retention in the solid byproducts and the pH. The present findings could be valuable for industrial application of characterizing and optimizing mercury control in wet FGD systems.